2014
DOI: 10.5665/sleep.3932
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sleep Apnea without High Pretest Probability or with Comorbidities by Three Nights of Portable Sleep Monitoring

Abstract: Guerrero A, Embid C, Isetta V, Farre R, Duran-Cantolla J, Parra O, Barbé F, Montserrat JM, Masa JF. Management of sleep apnea without high pretest probability or with comorbidities by three nights of portable sleep monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…[28,29] However, Guerrero and colleagues reported that a 3-night PM was also accurate in ambulatory patients with mild comorbidities. [30] Our study expands on these results because the patients included in our study not only had more serious comorbidities, but they were also acutely ill; and yet, we were able to show that PM was as accurate in these patients as it is in stable patients tested at home.…”
Section: Discussionmentioning
confidence: 58%
“…[28,29] However, Guerrero and colleagues reported that a 3-night PM was also accurate in ambulatory patients with mild comorbidities. [30] Our study expands on these results because the patients included in our study not only had more serious comorbidities, but they were also acutely ill; and yet, we were able to show that PM was as accurate in these patients as it is in stable patients tested at home.…”
Section: Discussionmentioning
confidence: 58%
“…Based on current recommendations, the preponderance of the available literature has assessed the use of home sleep testing primarily in clinic-based populations with a high pretest probability of the disease. In the only available study exploring the use of home sleep testing in subjects with a low pretest probability, 16 it was demonstrated that three nights of home sleep testing can effectively and economically diagnose obstructive sleep apnea. However, given that a sleep clinic sample was assessed and the enrolled patients were not subjected to a standardized pretest assessment of risk, the results of that study are not generalizable to other patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a type 3 portable monitoring (PM) device (Stardust II Sleep Recorder; Philips Respironics, Inc.) has been recommended for use in a clinical environment if the recordings are reviewed manually (21). However, the use of PM also has limitations, since the device is sophisticated and causes patient discomfort, as a finger probe, nasal cannula and belt must be attached to the body (24). In addition, PM is not recommended in suspected OSA patients with comorbid conditions, such as insomnia, depression and mania, which may mask symptoms of OSA (25).…”
Section: Discussionmentioning
confidence: 99%